Green Entrepreneurial Orientation in MSMEs: A Systematic Review and Future Research Agenda - Erma Wijayanti; Budiman Abdulah; Dewa Putu Yohanes Agata L Sandopart (Universitas muhammadiyah malang, 2025)
This study presents a systematic review and bibliometric analysis of Green Entrepreneurship Orientation (GEO) in micro, small, and medium enterprises (MSMEs) for the period 2018–2025. The analysis employs a combined protocol with bibliometric techniques to identify research trends, author collaboration patterns, and thematic focuses. Findings indicate that key drivers of GEO in MSMEs include environmental awareness, innovation capacity, and stakeholder pressure, while under-explored areas include green technology adoption, policy support, and sustainable supply chain integration. This study proposes a future research agenda focused on digital transformation, circular economy practices, and SME resilience in a post-crisis context.